Creep, leap, crunch! : a food chain story - Shaffer, Jody Jensen (Alfred A. Knopf, 2023)
"In this nonfiction picture book, discover how the animal kindgdom's food chain takes shape, from the lowly worm to the mighty king of the jungle" --